Genetic structure of Zeugodacus tau (Walker) in relation to cucurbit host plants - Duangta Julsirikul; Sangvorn Kitthawee (Agriculture and Natural Resources, 2021)
Zeugadacus tau (Walker) (Diptera: Tephritidae) is a polyphagous fruit pest that causes damage to agricultural and wild crops, especially in the family Cucurbitaceae. Z. tau is a complex species with a high level of genetic variation. The genetic structure was investigated of Z. tau populations collected from 10 different plant species using single strand conformation polymorphism (SSCP) analysis of the mitochondrial cytochrome c oxidase I (COI) sequences. In total, 489 Z. tau individuals showed 18 SSCP haplotype patterns, with a high level of genetic diversity. The clustering of COI sequences on the maximum likelihood tree and a haplotype network was consistent and showed that the Z. tau population collected from the wild crop of Trichosanthes tricuspidata had fixed haplotypes that were not found in Z. tau from agricultural crops. In addition, these fixed haplotypes were genetically different from the other haplotypes and are likely the cause of the genetic structure among Z. tau populations. The analysis of molecular variance revealed a significant genetic structure of Z. tau from cucurbit host plants (F-statistics [FST] = 0.6625, p < 0.01). Therefore, it can be concluded based on the sample populations used in this study that host plants play an important role in genetic differentiation among Z. tau populations and may be informative for genetic variation of other polyphagous insect pests to facilitate more efficient control and management.